Hubungan Kedisipinan Belajar Dirumah Dengan Prestasi Belajar Siswa Kelas VII Pada Mata Pelajaran PAI di SMPN 1 Tigo Nagari - Ririn Juli Anggraini; Junaidi Junaidi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The authors were inspired to conduct this study after noticing a variety of issues among SMPN 1 Tigo Nagari pupils, particularly in PAI classes. These issues persist despite the school's best efforts to enforce discipline. The problem is that some students continue to arrive late to class, others consistently disobey rules, and others still resort to slurs in their everyday interactions with one another. Still, there are those well-behaved students whose academic performance falls short of standards. The goal of this research was to find out if there was a connection between parental discipline and academic success at SMPN 1 Tigo Nagari.Pearson Product Moment was used for the quantitative correlation analysis in this study. SMP N 1 Tigo Nagari is the site of this investigation. All 160 pupils from grades VII.A through VII.E were included in the analysis. Forty students were selected using proportional random selection for this investigation. The writer employed all of seventh grade as a research sample, selecting eight students at random from each of two classes. Most pupils have already completed some level of general education. A questionnaire was the method of data collection in this study.Based on the data analysis, the study found no statistically significant correlation between students' home study habits and their academic performance.